Periodization of the Reign of Alexander I in Soviet Historiography - A. V. Chernov; V. V. Blokhin (Научный диалог, 2020)
The problem of the periodization of the reign of Emperor Alexander I in the works of Soviet historians is considered. The relevance of the study is due to the fact that even now the question of the periodization of this period causes controversy among scientists. Understanding that any periodization is conditional, which has emerged among modern historians, requires a revision of various approaches to the periodization of history. As part of the study, a review of a wide range of historiographic sources was carried out, which included special studies devoted to the reign of Alexander I, as well as generalizing works and textbooks that characterize this period of Russian history. The novelty of the research is seen in the fact that for the first time in Russian historiography, it is analyzed how researchers solved the issue of the periodization of the Alexander I reign throughout the Soviet period. Various approaches to the periodization of Russian history in the first quarter of the 19th century are revealed. Their development has been traced throughout the entire existence of the Soviet state. Particular attention is paid to the contradictions that take place in the approaches to the periodization of the reign of Alexander I, proposed by Soviet historians.